2014
DOI: 10.15590/ajase/2014/v3i7/53576
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Effectiveness of Learning Chatbot Systems on Student's Learning Outcome and Memory Retention

Abstract: Creating a learning environment in which students learn more effectively remains the great challenge from decades; different approaches are proposed, for example, Intelligent Tutoring Systems, Question Answering System and chatbot. All these approaches used natural language to achieve that goal. A comparison of these systems viz-a-viz student learning outcome and behavior is of eminent importance. To achieve this goal a chatbot system with knowledge base for Object-Oriented Programming Languages is developed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 14 publications
3
12
0
2
Order By: Relevance
“…program, chatbot, might also be an effective feature to be introduced in writing assessments if one uses it to ask for question and answer exchanges to check, clarify, and receive relevant information while completing a writing task. An empirical study has found that these question-andanswer exchanges with the chatbot were more effective than the Internet search engines because the learners showed a longer memory retention (Abbasi & Kazi, 2014). Looking into the effects of such A.I.…”
Section: Suggestion For Future Studiesmentioning
confidence: 99%
“…program, chatbot, might also be an effective feature to be introduced in writing assessments if one uses it to ask for question and answer exchanges to check, clarify, and receive relevant information while completing a writing task. An empirical study has found that these question-andanswer exchanges with the chatbot were more effective than the Internet search engines because the learners showed a longer memory retention (Abbasi & Kazi, 2014). Looking into the effects of such A.I.…”
Section: Suggestion For Future Studiesmentioning
confidence: 99%
“…A chatbot is developed to measure the memory retention and learning outcome of students [29]. A chatbot of an object-oriented programming language is developed and is deployed.…”
Section: Knowledge Evaluation Through Conversationmentioning
confidence: 99%
“…Previous studies showed that the technology has the potential to assist attitude learning, which involves cognitive, affective, and behavioral aspects. Regarding the cognitive aspect, prior works have revealed the effectiveness of the CI in memory retention [1], critical thinking, and inquiring mindsets [23]. A CI is known to improve students' affective learning outcomes [62] and influence users' behaviors through distraction and encouragement [32].…”
Section: Leveraging Conversational Interfaces For Sexual Harassment Prevention Trainingmentioning
confidence: 99%